2023
DOI: 10.1021/jacs.3c04662
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Generation of Aryl Carbocations from Phenols in Aqueous Microdroplets: Aromatic SN1 Reactions at the Air–Water Interface

Abstract: Although phenol is stable in bulk water, we report an exceptional phenomenon in which phenol is spontaneously transformed into a phenyl carbocation (Ph+) in water microdroplets. The high electric field at the air–water interface is proposed to break the phenolic Csp2–OH bond, forming Ph+, which remains in equilibrium with phenol as deciphered by mass spectrometry. We detected up to 70% conversion of phenol to Ph+ in aqueous microdroplets, although catalyst-free activation of the phenolic Csp2–OH bond is challe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…The partial solvation is thus helpful in alleviating nucleophilic attack by the solvents until they are eventually released into gaseous phase via desolvation. We also note the viable mechanism proposed by Banerjee et al, in which the survival of the cationic intermediates is ascribed to the formation of intimate or tight ion pair (R + X – , R + for the cationic intermediates and X – for their counteranions) in the vanishing droplets. Similarly, such Coulomb interactions might have also played a role in hindering their reactions with nucleophiles.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The partial solvation is thus helpful in alleviating nucleophilic attack by the solvents until they are eventually released into gaseous phase via desolvation. We also note the viable mechanism proposed by Banerjee et al, in which the survival of the cationic intermediates is ascribed to the formation of intimate or tight ion pair (R + X – , R + for the cationic intermediates and X – for their counteranions) in the vanishing droplets. Similarly, such Coulomb interactions might have also played a role in hindering their reactions with nucleophiles.…”
Section: Results and Discussionmentioning
confidence: 99%
“…In this circumstance, the outer layer is rich in protons that can act as a superacid, forming stable diarylcarbenium ions. 54,55 Other studies 56 opine that aromatic compounds in microdroplets preferentially inhabit the air-water interface, positioning the aromatic ring towards the air side while the -OH group remains embedded in water. Such a high electric eld has the potential to break the C-O bond, thus leading to the production of the diarylcarbenium ions at the interface of the microdroplet.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, they found that the droplet surface electric fields of ∼0.16 V/Å yield enough power to lower the activation energy and accelerate the rates of chemical reactions by several orders of magnitude. Indeed, Nandi et al found that water droplets can generate aryl carbocations from phenols by an aromatic S N 1 reaction, which is presumably accelerated by the protonation capability of the droplet. More recently, Zhang, Xie et al reported that water droplets accelerate, by 7 orders of magnitude, the Menshutkin S N 2 reaction between pyridine and CH 3 I.…”
Section: Use Of Water Microdroplets To Accelerate Reactionsmentioning
confidence: 99%